Dietary protein requirements of whiteleg shrimp (Penaeus vannamei) post-larvae during nursery phase in clear-water recirculating aquaculture systems - Barreto, André; Silva, Andreia; Peixoto, Diogo; Fajardo, Carlos; Pinto, Wilson; Rocha, Rui J. M.; Conceição, Luís E. C.; Costas, Benjamín (Frontiers in Marine Science, 2023)
Whiteleg shrimp Penaeus vannamei farming in clear water recirculating aquaculture systems (RAS) is relatively recent, and consequently, knowledge on the shrimp dietary demands is still insufficient, particularly in the initial developmental stages. This study aimed at assessing the dietary protein requirement of whiteleg shrimp post-larvae (PL) in a clear-water recirculating aquaculture system (RAS). Six microdiets were formulated to contain 34%, 44%, 49%, 54%, 58%, and 63% crude protein (P34, P44, P49, P54, P58 and P63, respectively) and were evaluated in triplicates. Whiteleg shrimp PL (3.2 mg wet weight) were reared for 21 days in a clear-water RAS at Riasearch Lda. At the end of the feeding period, the optimal protein requirement was estimated at 47.1%, 46.4%, 47.2%, and 44.0% for weight gain, relative growth rate (RGR), feed conversion ratio (FCR), and survival, respectively. PL fed the P54, P58, and P63 diets achieved significantly higher final body weights than those fed P34. PL fed P34 showed significantly lower RGR and survival and significantly higher FCR values than those fed the remaining diets, suggesting that low protein diets may not be adequate to be used in this stage of shrimp development and/or for the clear-water RAS husbandry conditions. Moreover, diet P34 seemingly reduced the overall antioxidant status of the PL when compared to P44, P49, and P54. However, the P34 diet seems to have stimulated the PL immune mechanisms when compared to P44, P49, and P54, possibly due to increased levels of fish and algae oil. Similarly, despite the good growth performances, a diet containing 63% of protein also seemed to have compromised the overall shrimp PL antioxidant status and stimulate their immune system. Shrimp fed diet P54 showed an apparent overall superior antioxidant status when compared to the remaining diets, evidencing that using protein inclusion levels up to 54% in aquafeeds not only potentiates growth performances and survival but also can potentially be beneficial to the health status of P. vannamei PL grown in a clear-water RAS. Hence, results from this study suggest that a minimum of approximately 47% of protein should be considered when tailoring microdiets for whiteleg shrimp PL grown in a clear-water RAS, but inclusion levels up to 54% can be used with benefits to the PL antioxidant status.